Mycobacterium avium subsp. paratuberculosis viability determination using F57 quantitative PCR in combination with propidium monoazide treatment - Kralik, P; Nocker, A; Pavlik, I (International journal of food microbiology, 2010)
Mycobacterium avium subsp. paratuberculosis (MAP) is known to be a very slow-growing organism. The fact that cells typically need several weeks to form visible colonies severely compromises the suitability of plate counting for assessment of viable cell counts. This problem might be overcome by the application of fast molecular methods containing a viability component. We have evaluated a promising technology combining sample treatment with propidium monoazide (PMA) prior to DNA extraction for selective detection of cells with intact cell membranes with detection of sequence element F57 by quantitative PCR (F57 qPCR). Element F57 is unique for MAP and is not known to exist in any other bacterial species. Conditions of PMA treatment were optimised for MAP isolate 7082 using live and heat-killed cells and comparing different DNA extraction procedures. The subsequent successful application of the optimised protocol to four other MAP isolates of different origins suggested that the optimised protocol might be broadly applicable to different MAP strains. Furthermore, different equations were compared to use the data resulting from this technology to optimally predict the percentage of live MAP cells in mixtures containing both live and dead cells. The presented protocol holds promise to be used routinely for detecting MAP with intact cell membranes in research applications.
Keywords: vaječný žloutek; azidy; polymerázová řetězová reakce; Bacterial Load; mikrobiální viabilita; Azides; Mycobacterium avium subsp. paratuberculosis; potravinářská mikrobiologie; Egg Yolk; Food Safety; propidium; Cell Membrane; Propidium; DNA, Bacterial; DNA bakterií; Microbial Viability; Food Microbiology; buněčná membrána; bezpečnost potravin; Polymerase Chain Reaction; bakteriální nálož